RESEARCH OF UV-PROTECTIVE ACTIVITY OF FERULIC ACID AS PART OF OINTMENT COMPOSITIONS WITH DIFFERENT PHYSICAL AND CHEMICAL PROPERTIES - I. L. Abisalova; E. P. Fyodorova; E. A. Maslovskaya (Фармация и фармакология (Пятигорск), 2015)
Cosmetics with the ability to neutralize harmful influence of ultraviolet rays on skin are quite in demand. UV filters in creams composition are divided into two groups: physical and chemical. Antioxidants are used as chemical UV filters. The article presents the results of ferulic acid testing as UV filter in ointment bases with lipophile, hydrophile and lipophilic and hydrophilic properties. The dependence of ferulic acid efficiency from the base type where it was applied was established. The results received are correlated with data about release rate of ferulic acid received in vitro. Ointment bases with such emulsifiers as cetyl alcohol, base emulsifier and Olivem 1000 have the most signified UV protective effect of ferulic acid.